2022
DOI: 10.3390/su14148401
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Embodied Environmental Attributes of Construction in Metropolitan and Growth Region of Melbourne, Australia to Support Urban Planning

Abstract: As growth regions evolve to accommodate the increasing population, they need to develop a wider variety of residential properties to accommodate the varying needs of the residents. As a result, the new accommodation is denser which involves higher embodied water carbon and energy. This research compares the construction differences in metropolitan and growth regions of Melbourne to identify embodied carbon, water, and energy. Representative areas of 25 km2 are selected from both regions. The growth region has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…With population growth in metropolitan and regional areas in Australia, there is a wider development in residential properties that in turn contributes to higher embodied carbon [18]. There have been several studies conducted on EC in the residential sector in Australia.…”
Section: Embodied Carbon In the Residential Sector In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…With population growth in metropolitan and regional areas in Australia, there is a wider development in residential properties that in turn contributes to higher embodied carbon [18]. There have been several studies conducted on EC in the residential sector in Australia.…”
Section: Embodied Carbon In the Residential Sector In Australiamentioning
confidence: 99%
“…Ref. [18] identified that building materials such as structural steel, concrete, composite concrete, and rebar have higher levels of embodied carbon compared to timber in metropolitan areas, as opposed to regional areas, in Australia. This discrepancy was mainly attributed to the growth of residential construction in regional areas.…”
Section: Embodied Carbon In the Residential Sector In Australiamentioning
confidence: 99%
“…There are more cities and countries still struggling to establish a clear agenda and consistent policy regarding the implementation of UGI. There is a clear consensus among the researchers that the reasons for the slow progress of UGI development are mainly because of the competition for space in cities, the difficulty of finding finance, uncertainty regarding the economic benefits of GI, the complexity of dealing with a living infrastructure, a lack of policy and standardized practices, slow adoption and a lack of awareness of new ideas [28][29][30][31][32]. It is necessary to further investigate the current practice of UGI for thermal comfort to provide more information related to UGI practices, to achieve a better understanding of UGI designs, the appropriate methods, performance evaluations, and the potential parameters that can be achieved.…”
Section: Research Objectivesmentioning
confidence: 99%
“…Synthetic aperture radar (SAR) satellites can acquire images of specified areas of the Earth’s surface at observation requests with all-day and all-weather imaging capacity [ 1 , 2 ]. Image products acquired by SAR satellites are widely used in many fields, such as emergency response in environments [ 3 ], target recognition and classification [ 4 ], urban planning and architectural layout [ 5 ], and crop detection and disaster prevention [ 6 , 7 ]. With the enhancement of imaging capabilities of SAR and the rapid growth in the number of SAR satellites, customers are increasingly demanding timeliness in SAR image acquisition [ 8 ].…”
Section: Introductionmentioning
confidence: 99%